Brain Derived Neurotropic Factors in Speed vs. Inclined Treadmill in Young Adult Healthy Male With Occult Balance Disorder - Yulinda, Stephanie T.; Tinduh, Damayanti; Wardhani, Lukitra; Laswati, Hening; Wibisono, Sony; Soenarnatalina, Melaniani (Frontiers in Integrative Neuroscience, 2019)
Background: Fall risk has increased among elders and young adult sequentially prior to any cause. Occult balance disorder may become one of the morbidity cause of fall in young adult and eventually to elders. Occult balance can be predicted by one leg stance test as an evidenced test to measure static balance function which leading to dynamic balance function. Treadmill exercise has been proven as a dynamic balance exercise aside from cardiopulmonary exercise. As inclination and speed are the components of treadmill exercise, supposingly increase the balance function through the the act of brain derived neurotropic factor (BDNF). Brain derived neurotropic factor (BDNF) was one of tropic hormones produced in neuron, muscle, hematopoietic tissue characterized in neurons morphology regulation and neuroplasticity. Material and method: 20 healthy young adult men were included, divided to inclination and speed treadmill exercise groups. We observed the immediate effect of serum BDNF in blood as first blood drawn for BDNF taken before exercise and 30 minutes after exercise at the first training, second blood drawn taken before exercise and 30 minutes after exercise at the last training in 2nd week completion of treadmill exercise. Result: Significant increased of serum BDNF value in speed group before exercise first day and before exercise last day (p=0,001), after exercise first day and after exercise last day (p=0,001). No significant increase of BDNF serum at speed group before exercise first day and after exercise first day (p=0,159), before exercise last day and after exercise last day (p=0,892). There were no significant increase BDNF serum at inclination group at all parameters (p>0,05). BDNF serum was an actual neurotropic factor affect not only neuronal system, but also molecular energy and metabolism regulation. BDNF serum production depend on the aerobic capacity, lactate production, muscle calcium uptake, and muscle fiber type used in exercise. Treadmill exercise with gradual speed increase the BDNF serum in blood stream that also reflect the BDNF percentage in brain. Conclusion: Treadmill exercise with gradual escalation of speed increase the BDNF serum